Fotocatálise heterogênea de enterococcus faecalis e pseudomonas aeruginosa desencadeada pela ação da luz UV e branca em espátulas com revestimento de nanopartículas TiO2 e Ag - Porto, Cecília Helena Soares [UNESP]; Santos-Pinto, Ary dos [UNESP]; Silva, Elson Longo da [UNESP]; Pizzolito, Antônio Carlos [UNESP]; Porto Neto, Sizenando de Toledo [UNESP] (My University, 2011)
Nanotechnology, the science of minuscule, has developed products which are able t o manipulate atoms and molecules that could be applied in the sterilization process of dental instruments. Objetives: The objective of the present study was to evaluate the self-cleaning action of TiO2 and Ag nanoparticles coating on dental instruments by the photocataliys process under UV and visible light irradiation. Material and method: Microbiologic tests were done using dental cement spatulas coated with TiO2 and Ag nanoparticles (one or three layers), and contaminated with 10 mcrl of Pseudomonas aeruginosa and Enterococcus faecalis, respectively. After contamination, they were exposed to ultraviolet light and visible light for 120 minutes. Next, they were transferred to and stored in test tubes with BHI (Brain Heart Infusion) and incubated in 35 to 37 °C. Checking times for bacterial growth and for control and retrieval tests were done at: 24, 48, 72 and 96 hours. Result: The Pseudomonas aeruginosa was inactive after 120 minutes of ultraviolet light irradiation, thus confirming the heterogeneous photocatalytic activity of TiO2 and Ag. The Pseudomonas aeruginosa was not inactivated under visible light irradiation and the Enterococcus faecalis was not inactivated under UV and visible light irradiation of the dental cement spatulas coated with TiO2 and Ag nanoparticles in the readings to 96 hours, showing bacterial growth. Conclusion: There were no influence of one or three layers of TiO2 and Ag nanoparticles coating of the spatulas in the results. The heterogeneous photocatalysis activity of TiO2 and Ag under UV light irradiation was confirmed for Pseudomonas aeruginosa but not under visible light. Enterococcus faecalis did not confirmed the photocatalytics activity of TiO2 and Ag under UV light irradiation and visible lights irradiation.

Nanotecnologia, ciência do minúsculo, gera produtos capazes de manipular átomos e moléculas com aplicação no processo de esterilização de instrumentais odontológicos. Objetivo: Avaliar a ação autolimpante e esterilizante do processo de fotocatálise heterogênea desencadeado pela ação da luz UV e branca sobre o recobrimento de instrumentos odontológicos com nanopartículas de TiO2 e Ag. Material e método: Foram realizados testes bacteriológicos em espátulas odontológicas revestidas com nanopartículas de TiO2 e Ag (uma ou três camadas) e contaminadas com 10  mcrl dos microrganismos Enterococcus faecalis e Pseudomonas aeruginosa. Após contaminação, as espátulas foram expostas à luz UV e branca por 120 minutos, transferidas para tubos contendo meio BHI e incubadas a 35-37 °C. Foram feitas leituras em intervalos de 24, 48, 72 e 96 horas para verificação do crescimento das bactérias e testes de controle e recuperação. Resultado: A Pseudomonas aeruginosa foi inativada após exposição de 120 minutos à luz UV, indicando a ocorrência do processo de fotocatálise heterogênea no recobrimento de nanopartículas de TiO2 e Ag das espátulas. A Pseudomonas aeruginosa não foi inativada pela exposição à luz branca e o Enterococcus faecalis não foi inativado pela exposição à luz UV e à branca nas espátulas de cimento odontológico recobertas com nanopartículas de TiO2 e Ag, nas leituras de até 96 horas, ocorrendo o crescimento bacteriano. Conclusão: Não houve influência do revestimento das espátulas com uma ou três camadas de nanopartículas de TiO2 e Ag nos resultados. A fotocatálise heterogênea da Pseudomonas aeruginosa foi confirmada pela exposição à luz UV da espátula com revestimento de TiO2 e Ag, mas não pela luz branca. A fotocatálise heterogênea do Enterococcus fecalis não foi confirmada tanto pela exposição do TiO2 e Ag à luz UV como à branca.
Heterogeneous photocatalysis of enterococcus faecalis and pseudomonas aeruginosa activated by the action of UV and visible light on dental instruments with TiO2 and Ag nanoparticles coating
Keywords: Silver and titanium dioxide nanoparticles; Heterogen fotocatalises; Dental instruments sterilization; Bacterial tests; Visible and ultraviolet light; Nanoparticulas de dióxido de titânio e prata; Fotocatálise heterogênea; Testes bacteriológicos; Luz ultravioleta e branca